Distribution of Daily Use Local Language in Indonesia - Suparman Ibrahim Abdullah; . Yunita; Maria C. (International Conference on Education and Language (ICEL), 2014)
Indonesia is a pluralistic country, composed of many ethnic, religious affiliation, diverse arts and culture, use of language in everyday situations scattered throughout the archipelago. It is to inspire social and cultural programs that are very complex. While the development of infrastructure and economic development is interrupted, due to the distortion of the political developments in Indonesia.Development issues related to education , specifically in Indonesian language should be designed better .This paper discusses the prevalence of daily use of vernacular languages in Indonesia . In particular the spoken language used by speakers of most languages there are nine . The ninth language speakers dispersal shifting all over the archipelago during the 40 years 1980 -2010 . This language is Batak , Balinese , Bugis,Banjar , Madura , Malay , Minangkabau , Sundanese , Javanese .